2017
DOI: 10.1039/c6ta08287d
|View full text |Cite
|
Sign up to set email alerts
|

The direct hydrothermal deposition of cobalt-doped MoS2 onto fluorine-doped SnO2 substrates for catalysis of the electrochemical hydrogen evolution reaction

Abstract: Metal chalcogenides, and doped molybdenum sulfides in particular, have considerable potential as earth-abundant electrocatalysts for the hydrogen evolution reaction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
26
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 46 publications
(27 citation statements)
references
References 53 publications
1
26
0
Order By: Relevance
“…It was found that the HER activity of Mo 2 C materials can be signicantly improved by fabrication of Mo 2 Cbased heterostructures such as Mo 2 N-Mo 2 C, 14,15 MoC-Mo 2 C, 16 Ni/Mo 2 C-PC, 17 NiMo 2 C/NF, 18 Mo x C/Ni, 19 nw-W 4 Mo, 20 and others. [21][22][23][24][25][26] The high activity of these heterostructures derives from synergistic electron transfer and mass transfer phenomena.…”
Section: Introductionmentioning
confidence: 99%
“…It was found that the HER activity of Mo 2 C materials can be signicantly improved by fabrication of Mo 2 Cbased heterostructures such as Mo 2 N-Mo 2 C, 14,15 MoC-Mo 2 C, 16 Ni/Mo 2 C-PC, 17 NiMo 2 C/NF, 18 Mo x C/Ni, 19 nw-W 4 Mo, 20 and others. [21][22][23][24][25][26] The high activity of these heterostructures derives from synergistic electron transfer and mass transfer phenomena.…”
Section: Introductionmentioning
confidence: 99%
“…A Δ G H close to zero is favorable and indicates that hydrogen adsorption is neither too weak nor too strong, and this value correlates with exchange current densities that are a good approximation for HER activity. Site engineering by nanostructuring is required to achieve a high density of edge sites to overcome the limitations of the naturally occurring semiconducting hexagonal molybdenite (2H‐MoS 2 ) phase, which is a remarkably inactive electrocatalyst in the bulk form . However, nanostructuring tends to impair the long‐term stability of the electrocatalyst, which reduces the operational lifetime significantly .…”
Section: Introductionmentioning
confidence: 99%
“…[12,13] A DG H close to zero is favorable and indicates that hydrogen adsorption is neithert oo weak nor too strong, and this value correlates with exchange current densities that are ag ood approximation for HER activity.S ite engineering by nanostructuring is requiredt oa chieve ah igh density of edge sites to overcomet he limitations of the naturally occurring semiconductingh exagonal molybdenite (2H-MoS 2 )p hase,w hich is ar emarkably inactive electrocatalysti nt he bulk form. [14][15][16][17][18][19] However, nanostructuring tends to impair the long-term stability of the electrocatalyst, which reduces the operational Thee lectrocatalytic hydrogen evolution reaction (HER) is of central importance for the production of H 2 from sustainable sources.C urrently,Pti st he best electrocatalystf or this transformation, but other materials based on less-precious elements are now attracting increased attention. Of these alternatives,t he molybdenum chalcogenidess how particular promise.…”
Section: Introductionmentioning
confidence: 99%
“…Several forms of molybdenum sulfide such as amorphous MoS x [21,22], crystalline MoS 2 [23,24], sulfur-rich [25,26] or sulfur-deficient [27,28] MoS 2 , and metal-promoted MoS 2 [29] have been synthesized on conducting substrates via simple solution-based chemical techniques that includes drop-casting, dip-coating, hydrothermal, and electrodeposition. Such HER electrocatalysts achieved a Tafel slope in the range of 39-95 mV dec −1 and overpotential in the range of 150-300 mV at 10 mA cm −2 [30].…”
Section: Introductionmentioning
confidence: 99%